Development and simulation analysis of a new perishable inventory model with a closing days constraint under non-stationary stochastic demand. (April 2018) - Janssen, Larissa; Sauer, Jürgen; Claus, Thorsten; Nehls, Uwe
Highlights: We develop a new inventory model with closing days constraint for grocery retail. In the simulation study, we test the developed model in grocery stores under a rolling planning. We analyze the influence of closing days constraint on waste quantity and total costs. We determine that closing days constraint makes the inventory management more efficient. Abstract: The food waste in grocery retail is a worldwide problem. Many mathematical inventory models for perishable items do not have a closing days constraint, although the age of perishable items also increases on closing days in grocery stores. We develop a new age-based inventory model with a closing days constraint. This stochastic multi-item inventory model includes total stock capacity constraints, a positive lead time, a periodic inventory control, a target customer service level and mixed FIFO and LIFO issuing policies for perishable items with a fixed lifetime under a non-stationary random demand. We show in a comparative simulation study under a rolling planning that the closing days constraint improves order decisions and reduces waste quantities and costs in grocery stores.